Role of X-linked genes on sex differences in neurogenin 3 expression in developing hypothalamic neurons - Cisternas, Carla Daniela (2016)
Fil: Cisternas, Carla Daniela. Universidad Nacional de Córdoba. Facultad de Odontología. Cátedra de Biología Celular; Argentina.